2022
DOI: 10.1097/gox.0000000000004448
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Same-day Discharge after Immediate Alloplastic Breast Reconstruction: A Systematic Review

Abstract: Background: Implant-based breast reconstruction can be accomplished in a variety of ways and can result in vastly different postoperative experiences for patients. The COVID-19 pandemic and recent trends have resulted in a shift toward outpatient management of these patients. Methods: A systematic review of PubMed and Embase databases was conducted. A total of 1328 articles were identified on initial search, and after several rounds of review, a total of four met inclusion and exclusion criteria. Manuscripts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
(78 reference statements)
3
13
0
Order By: Relevance
“…A recent systematic review with a total of 285 same-day discharge patients found that ERAS protocols after immediate alloplastic breast reconstruction had no difference in overall complication rates, including hematomas, between same-day discharge and overnight admission patients. 19 In our study, only 1 TE-IBR patient and 1 oncoplastic breast reconstruction patient developed postoperative hematomas, which aligns with findings reported in the literature. With over a year's worth of same-day discharge patients, we can confidently demonstrate that there is no change in hematoma rates and subsequent outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A recent systematic review with a total of 285 same-day discharge patients found that ERAS protocols after immediate alloplastic breast reconstruction had no difference in overall complication rates, including hematomas, between same-day discharge and overnight admission patients. 19 In our study, only 1 TE-IBR patient and 1 oncoplastic breast reconstruction patient developed postoperative hematomas, which aligns with findings reported in the literature. With over a year's worth of same-day discharge patients, we can confidently demonstrate that there is no change in hematoma rates and subsequent outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, surgeons may be hesitant to discharge their patients home the day of surgery because of the risk of forming a hematoma in the immediate postoperative period and delaying treatment. A recent systematic review with a total of 285 same-day discharge patients found that ERAS protocols after immediate alloplastic breast reconstruction had no difference in overall complication rates, including hematomas, between same-day discharge and overnight admission patients 19 . In our study, only 1 TE-IBR patient and 1 oncoplastic breast reconstruction patient developed postoperative hematomas, which aligns with findings reported in the literature.…”
Section: Discussionsupporting
confidence: 90%
“… 29 31 Mastectomy with prosthetic reconstruction also has been shown to have equivalent readmission rates for ambulatory versus hospital-based procedures, and recent evidence from the COVID-19 pandemic has demonstrated that mastectomy with reconstruction can be performed on an ambulatory/outpatient basis without compromising safety or the patient experience. 7 , 15 , 16 , 18 , 32 34 Indeed, this ongoing experience demonstrates no difference in complications when mastectomy is performed in an ambulatory setting with or without prosthetic reconstruction.…”
Section: Discussionmentioning
confidence: 77%
“…Our findings differ from those of other studies in the surgical safety literature, which show that patient-level factors are indeed a significant predictor of postoperative readmissions. 18 , 19 In the breast surgical oncology literature, black race and higher American Society of Anesthesiologists class are shown to be significant factors of readmission. 5 In colorectal surgery, minority-serving hospitals have higher readmission rates than non-minority-serving hospitals, and patient-level factors account for 65 % of this difference.…”
Section: Discussionmentioning
confidence: 99%
“…By Marxen T, Shauly O, Losken A. Plast Reconstr Surg Glob Open 2022;10:e4448. 5 The authors present a systematic review assessing the safety of same-day patient discharge after immediate, alloplastic breast reconstruction. Four included studies provided data for a total of 574 patients.…”
Section: Hospital Universitario Monterrey Nuevo León Méxicomentioning
confidence: 99%